An assessment of integrated thinking levels among JSE-listed entities - Ecim, Dusan (My University, 2022)
Integrated thinking involves a holistic, multi-capital approach to decision-making and operations to promote value creation and sustainability. The IIRC has defined integrated thinking and promoted its value extensively. However, there is a lack of information, both in practice and in academic literature, dealing with how to implement and evaluate integrated thinking. This study assesses integrated thinking in terms of the definition, the benefits and challenges of implementation and the controls necessary to implement this concept. A model developed by Trialogue is then used to evaluate integrated thinking levels based on underlying principles/indicators. This framework is applied to a sample of 97 JSE listed entities’ integrated reports, and, using a qualitative content analysis approach, the framework is used to score the integrated thinking levels. Results reveal that entities in South Africa are scoring well on integrated thinking principles, primarily geared through the strong governance and reporting structures in place. Remuneration and performance management have, however, been identified as a weakness. Using an exploratory factor analysis, results reveal that three factors contribute to a high portion of the variance in integrated thinking. These factors are [1] managing of and reporting on value creation; [2] stakeholder awareness and corporate accountability; and [3] governance. This has revealed that entities are in different stages of integrated thinking application being an early/ developing stage, an emerging integrated thinking logic or a strong integrated thinking logic. Significant statistical relationships are identified between the factors and entity-specific metrics which point towards potential drivers of integrated thinking. An integrated thinking framework can be used as a practical tool by stakeholders to gauge and benchmark the level of integrated thinking taking place in an entity. An entity can also use this framework as a guiding tool on the steps needed to execute on various integrated thinking principles.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Commerce (Accounting), Faculty of Commerce, Law and Management, School of Accountancy
Keywords: UCTD; Integrated thinking; Integrated reporting; Sustainability; Report quality; IIRC; SDG-8: Decent work and economic growth